Perkembangan Hukum Cyber di Indonesia: Tantangan dan Peluang - H. Ajamalus; Agung Cucu Purnawirawan (Bulletin of Community Engagement, 2024)
The development of digital technology has brought substantial transformation to various aspects of life, including in the legal realm. In Indonesia, cyber law has experienced significant developments to overcome challenges that arise along with changes in technology and people's behavior in the digital space. These challenges include issues of cyber security, personal data protection, as well as increasingly complex cyber crimes. To respond to these challenges, Indonesia has made adjustments to the legal framework, including a revision of the ITE Law, which aims to increase protection for internet users and strengthen law enforcement in the cyber context. Although there are a number of obstacles such as competency gaps and legal adaptation to rapidly developing technology, these developments also provide great opportunities for digital economic growth and national cyber security.